Training of jurist in the 21st century from professional practice of lawyer’s perspective in a law firm - Sáez Castro, Daniel (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The training of a lawyer today necessarily involves not only inculcating knowledge, but also strengthening other skills that will be essential in their professional practice.